Comparing episodic memory outcomes from walking augmented reality and stationary virtual reality encoding experiences - Alvaro Pastor; Pierre Bourdin-Kreitz (Scientific Reports, 2024)
Abstract Episodic Memory (EM) is the neurocognitive capacity to consciously recollect personally experienced events in specific spatio-temporal contexts. Although the relevance of spatial and temporal information is widely acknowledged in the EM literature, it remains unclear whether and how EM performance and organisation is modulated by self-motion, and by motor- and visually- salient environmental features (EFs) of the encoding environment. This study examines whether and how EM is modulated by locomotion and the EFs encountered in a controlled lifelike learning route within a large-scale building. Twenty-eight healthy participants took part in a museum-tour encoding task implemented in walking Augmented Reality (AR) and stationary Virtual Reality (VR) conditions. EM performance and organisation were assessed immediately and 48-hours after trials using a Remember/Familiar recognition paradigm. Results showed a significant positive modulation effect of locomotion on distinctive EM aspects. Findings highlighted a significant performance enhancement effect of stairway-adjacent locations compared to dead-end and mid-route stimuli-presentation locations. The results of this study may serve as design criteria to facilitate neurocognitive rehabilitative interventions of EM. The underlying technological framework developed for this study represents a novel and ecologically sound method for evaluating EM processes in lifelike situations, allowing researchers a naturalistic perspective into the complex nature of EM.